Answer:
-x
Step-by-step explanation:
To find (x+1) substitue x+1 into the function.
1. 2(x+1)^2-5(x+1)+3: Substitution
2. 2x^2+4x+2-5x+5+3: First do binominal expansion theorem for 1st one then distrubtive property for the first and second one.
3.Combine like with like
, 4x+(-5x)= -x, 2-5+3=0 so
f(x+1)=
-x
B is the most likely independent
Answer:
- B) One solution
- The solution is (2, -2)
- The graph is below.
=========================================================
Explanation:
I used GeoGebra to graph the two lines. Desmos is another free tool you can use. There are other graphing calculators out there to choose from as well.
Once you have the two lines graphed, notice that they cross at (2, -2) which is where the solution is located. This point is on both lines, so it satisfies both equations simultaneously. There's only one such intersection point, so there's only one solution.
--------
To graph these equations by hand, plug in various x values to find corresponding y values. For instance, if you plugged in x = 0 into the first equation, then,
y = (-3/2)x+1
y = (-3/2)*0+1
y = 1
The point (0,1) is on the first line. The point (2,-2) is also on this line. Draw a straight line through the two points to finish that equation. The other equation is handled in a similar fashion.
Hey there!!
Okay so here are the steps....
(5 + 2i) + (8 - 3i) <---- when we have exponents we should worry about the "i" because it is equal to √-1 but here it isn't the case.
<u>
(13 - i)</u><u /> <----- This is the answer!
<u />I hope this helps! ^__^
The answer is C! the crossing of lines is the same on both sides